An Energy Based Multiaxial Fatigue Criterion - Gołoś, K. (Engineering Transactions, 1988)
The aim of this investigation was to develop a method of prediction of the multiaxial fatigue life. A form of the cyclic strain energy density is proposed as a damage parameter for multiaxial fatigue failure. The strain energy density includes both elastic and plastic strain energy densities, and it can be used to describe both the low- and high-cycle fatigue. The criterion proposed has an invariant property and is hydrostatic pressure sensitive. Predictions of the proposed criterion are compared with the experimental results of biaxial fatigue tests for the A-516 Gr. 70 carbon low - alloy steel. The comparison has shown good agreement.